PENYEBARAN WABAH DAN TINDAKAN ANTISIPATIF PEMERINTAH KOLONIAL DI SUMATRA’S WESTKUST (1873-1939) - Dedi Arsa (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Disease outbreaks (epidemics) affects human life broadly, overhauling the order of a society, and change thehistory. This paper discusses how the spread of epidemics in West Sumatra (Sumatra's Westkust) and treatment(anticipatory action) of the colonial government in the period 1873-1939. Epidemics that plague the WestSumatra during this period was recorded variously: smallpox, cholera, dysentery, beriberi, tuberculose, andinsanity (kringzingen). Outbreaks are caused by an unhealthy environment, poor dreinase, and low publicimune system. This aspect is compounded by social, economic and political unstablity. Anticipatory action takenby the colonial government by sending medical staffs to spot infected, reproduce vaccine, evacuate and relocatepatients to a more sterile, complete equipments in the hospital, and build additional hospitals.